Implementation of Digitalization Policies in Realizing Independent Villages from the Perspective of Agile Governance: A Case Study of Jedong Village, Pasuruan Regency - Hambali (Best Journal of Administration and Management, 2025)
This study aims to analyze the implementation of digitalization policies in fostering village independence, focusing on Jedong Village in Pasuruan Regency. Employing a qualitative descriptive approach, data were collected through direct observations, semi-structured interviews with village officials and residents, and analysis of relevant documents. The population comprises all stakeholders involved in the digitalization process, with a purposive sample of key informants selected based on their roles and experiences. The primary instrument used was an interview guide designed to elicit detailed information on the adoption and impact of digital tools. Findings indicate that the implementation of the Village Information System (SID) has significantly enhanced administrative efficiency, transparency, and community participation. Residents reported improved access to information and services, leading to increased engagement in village development initiatives. However, challenges such as limited internet infrastructure and varying levels of digital literacy among residents were identified as barriers to optimal utilization. The study concludes that while digitalization policies have the potential to promote village autonomy and development, addressing infrastructural and educational gaps is crucial for maximizing benefits. Recommendations include investing in digital infrastructure, providing training programs to enhance digital skills, and developing policies that support sustainable digital integration at the village level.